2007
DOI: 10.1029/2006gl029095
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationarity and reformation of high‐Mach‐number quasiperpendicular shocks: Cluster observations

Abstract: [1] A set of experimental data is presented for a highMach-number (M f = 5) quasiperpendicular (q Bn = 81°) bow shock layer crossed by Cluster spacecraft on 24 January 2001 at 07:05 -07:09 UT. The measurements of magnetic field, spectra of electric field fluctuations, and ion distributions reveal that the shock is highly nonstationary. In particular, the magnetic field profiles measured aboard different spacecraft differ considerably from each other. The mean frequency of downshifted waves observed upstream of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
86
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 25 publications
11
86
2
1
Order By: Relevance
“…This process is periodic, and is named self-reformation. Nonstationary characteristic of the shock front is later confirmed by an individual case study of Cluster observation at the terrestrial bow shock (Lobzin et al 2007). Mazelle et al (2010) statistically confirms this robust characteristic.…”
Section: Introductionmentioning
confidence: 76%
“…This process is periodic, and is named self-reformation. Nonstationary characteristic of the shock front is later confirmed by an individual case study of Cluster observation at the terrestrial bow shock (Lobzin et al 2007). Mazelle et al (2010) statistically confirms this robust characteristic.…”
Section: Introductionmentioning
confidence: 76%
“…However, although this problem was raised in the very beginning of collisionless shock physics, after more than four decades of research it is far from being well understood, most probably due to formidable difficulties of the experimental and theoretical analysis. A brief summary of the state of art can be found in the papers by Krasnoselskikh et al (2002) and Lobzin et al (2007), as well as in recent reviews (Hellinger, 2003;Lembege et al, 2004;Bale et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Horbury et al (2001) argue that these fluctuations stop before the ramp and do not appear to disrupt the shock structure; on the other hand, they don't reject the possibility that the fluctuations may be signatures of the unsteady shock reformation. The first convincing experimental evidence in favor of shock front reformation was presented by Lobzin et al (2007). Moullard et al (2006) were the first who probably observed another aspect of shock front nonstationarity -rippling.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to most studies of shock crossings being near the Earth where the Mach numbers typically range from low to modest (M A = 2-8). While some observations have been reported at Earth's bow shock [Lobzin et al, 2007], they remain open to interpretation [Comisel et al, 2011].…”
Section: Introductionmentioning
confidence: 99%